Perbandingan Nilai Struktur Tangga Konvensional Dengan Tangga Melayang Pada Bangunan Bertingkat - M, M. Afif (Universitas Negeri Surabaya, 2023)
The use of floating stairs at the international level is more than at the national level, due to the lack of knowledge about floating stairs owned by architects and contractors at the national level. Floating stairs are also still not widely used and are mostly used only to display the aesthetics of the building. So further research is needed when it is applied in the construction of a 5-storey multi-storey building. The research method used in this research is modeling using SAP2000 software which will produce a value for the strength of the building structure. Where the main structure is an open frame system and modeled as a 3D-space frame. In applying it to obtain the structural strength capacity of the column elements under review when loaded biaxially, the column element structures will be modeled in the form of a 5-storey multi-storey building. Obtained from the modeling that has been analyzed, for buildings with floating stairs, they have a very good role because they help to withstand dead loads, live loads, and earthquake loads, which can be seen from the displacement and drift ratio values ??that have been analyzed, so that they can be considered for building construction. building.